2006
DOI: 10.1158/1078-0432.ccr-05-2404
|View full text |Cite
|
Sign up to set email alerts
|

Signaling via ErbB2 and ErbB3 Associates with Resistance and Epidermal Growth Factor Receptor (EGFR) Amplification with Sensitivity to EGFR Inhibitor Gefitinib in Head and Neck Squamous Cell Carcinoma Cells

Abstract: Purpose: The epidermal growth factor receptor (EGFR) inhibitor gefitinib (Iressa) has shown antitumor activity in clinical trials against cancers, such as non^small cell lung cancer and head and neck squamous cell carcinoma (HNSCC). Research on non^small cell lung cancer has elucidated factors that may predict response to gefitinib. Less is known about molecular markers that may predict response to gefitinib in HNSCC patients. Experimental Design: We analyzed possible associations of responsiveness to gefitini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
175
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(189 citation statements)
references
References 41 publications
4
175
1
3
Order By: Relevance
“…353 Coexpression of ERBB3 with EGFR and ERBB2 348 or of ERBB2 and ERBB3 349 related to poor prognosis, and expression of ERBB3 was correlated with resistance to the EGFR inhibitor gefitinib. 354 Increases in ERBB3 along with EGFR and ERBB2 were also reported for papillary carcinoma of thyroid. 355,356 Involvement of ERBB3 in oral cancer was confirmed in a rat model, where Erbb3 protein was increased in carcinogen-induced oral carcinomas.…”
Section: Melanomasmentioning
confidence: 82%
“…353 Coexpression of ERBB3 with EGFR and ERBB2 348 or of ERBB2 and ERBB3 349 related to poor prognosis, and expression of ERBB3 was correlated with resistance to the EGFR inhibitor gefitinib. 354 Increases in ERBB3 along with EGFR and ERBB2 were also reported for papillary carcinoma of thyroid. 355,356 Involvement of ERBB3 in oral cancer was confirmed in a rat model, where Erbb3 protein was increased in carcinogen-induced oral carcinomas.…”
Section: Melanomasmentioning
confidence: 82%
“…44 This supports the theory that overexpressing EGFR cell lines are more likely to respond to EGFR targeting therapy. 45 In these cell lines combination treatments are thought to act synergistically because the cell lines utilize EGFR pathways like the PI3K and MAPK pathways to counteract the effect of radiation. 19 When these pathways are blocked, the cells become more sensitive to radiation.…”
Section: Methodsmentioning
confidence: 99%
“…These findings are consistent with several recent reports that suggest HER3 plays an important role in regulating tumor response to EGFR or HER2 targeting agents. Erjala et al (2006) demonstrated a correlation between HER3 expression and gefitinib resistance. Similarly, Fujimoto et al (2005) pointed to HER3 as a potentially important mediator of EGFR inhibition by gefitinib in NSCLC cells.…”
Section: Acquired Resistance To Egfr Inhibitionmentioning
confidence: 96%